The association between online pornography use and adolescents’ well-being - Þórunn Lea Sigurðardóttir 1999- (2022)
This study aimed to see whether there was a gender difference in online pornography use and whether or not watching online pornography had a relation to self-rated mental health, body image, parental control, parental support, and friends‘ support, among adolescents. The research question of this study was: “Does online pornography have negative effects on adolescents’ well–being and, are there gender differences in online pornography use?” The data used was from the Icelandic Centre for Social Research and Analysis (ICSRA) and the participants were adolescents in 8th-10th grade in Iceland. The data was from a cross-sectional census survey conducted in 2018 among all students in the 8th-10th grade in Icelandic grade schools. The survey was paper-based and distributed to all students at the same time. The questionnaire was anonymous. Regression analysis was used for statistical processing. The results showed a clear difference between the genders with boys being more likely than girls to watch online pornography. There was a significant relation between watching online pornography and self-rated mental health and friends’ support. Age was also a significant factor, the older the adolescents were, the more likely they were to watch online pornography. There was no significant relation between body image, parental control, and parental support. Keywords: Online pornography, adolescents, well-being, gender Tilgangur þessarar rannsóknar var að kanna hvort kynjamunur væri í notkun á netklámi og hvort það að horfa á netklám hefði tengsl við andlega heilsu á meðal unglinga, líkamsímynd, eftirlit foreldra og stuðning frá vinum og foreldrum. Rannsóknarspurning þessarar rannsóknar var: “Hefur netklám neikvæð áhrif á heilsu unglinga og er kynjamismunur í notkun á netklámi?” Gögnin sem voru notuð voru frá Rannsóknum og greiningu og þátttakendur voru unglingar í 8. – 10. bekk á Íslandi. Gögnin voru úr þversniðskönnun sem framkvæmd var árið 2018 á meðal allra nemenda í 8. – 10. bekk í íslenskum grunnskólum. Könnunin var á ...